Croatia Energy Sector Note - World Bank (World Bank, Washington, DC, 2019)
Croatia joined the European Union (EU) in 2013, and the energy sector has been undergoing liberalization, deregulation, and unbundling of state-owned energy utilities. Croatia haswelcomed a number of new public and private energy companies. The Croatian power exchange was established in 2014 and commenced operation in 2016 as a platform for electricity trade. This report reviews energy intensity (EI) and energy efficiency (EE) status in Croatia.